FEATURES VASCULAR REMODELING AND MARKERS OF IMMUNE-INFLAMMATORY RESPONSE IN PATIENTS WITH EH STAGE II - Фуштей, І.М.; Мочоний, В.О. (World of Medicine and Biology, 2015)
Clinical and pathogenetic significance of immuno-inflammatory response in the occurrence of coronary heart disease (CHD) in patients with essential hypertension (EH) is insufficiently studied. To determine the degree of vascular remodeling (MS) and its relationship with the concentration of immuno-inflammatory markers in blood plasma is a complex clinical and paraclinical study of 180 patients with essential hypertension (EH) II stage. Established that the velocity of the pulse wave (SHRPH) in aorto-femoral segment (ACC) was highest when combined CHD and GC (11,4 ± 0,5 m / s to 10,1 ± 0,2 m / s in patients with EH without CHD, p